MODELAGEM ESPAÇO-TEMPORAL DA INCIDÊNCIA DE DENGUE NA REGIÃO DA GRANDE VITÓRIA (RGV) - ES - LYRIO, Bruna Campos; MONROY, Nátaly Adriana Jiménez; MOLINARES, Fabio Alexander Fajardo (Brazilian Journal of Biometrics, 2019)
The State of Espírito Santo have suffered several dengue breakouts along the last decades, turning this disease into a major public health problem. According to the Brazilian Department of Health, in 2013, the State was fifth among the 11 States with the highest incidences of dengue. In 2016, the State was the third with higher incidence in Brazil. This work presents the space-time ARMA model as an alternative methodology for modeling the dengue incidence using data from the Greater Vitoria Region, Brazil. The model showed to be very suitable for the analyzed data. Spatial and temporal associations were identied, the incidence rates of the cities are directly in uenced by the rates observed in the closest neighbors as well as in the same city, until two months earlier.